Attribution and Ideology in American Politics: Causal Reasoning, Political Cognition, and Partisan Polarization in the Age of Trump - Leonard, Robert; Sunblad, Daniel; Thomas, Dan (Operant Subjectivity, 2021)
This research reports two Q-studies addressing the possibility that the partisan political divide defining contemporary American politics derives from differences in the way the Right and Left reason causally in addition to the more obvious content-specific contrasts in policy positions and the like. Attribution theory, the study of lay explanatory styles emphasizing either "internal" considerations â€” dispositional predilections of actors or "external" factors â€” broader environmental/contextual considerations â€” is employed in concourse compilation for two political controversies (economic inequality and electoral success in the 2016 presidential election), and two studies are reported. Results from the first demonstrate sharp differences between ideological and partisan opponents: Republican respondents display clear tendencies to employ dispositional attributions in accounting for economic inequality, praising the well-to-do as diligent and deserving for their success while denigrating the poor for their failure to compete in free-market capitalism. The second study amplifies and extends these findings by comparing Republican and Democratic accounts of the 2016 election results. Again, those on the Right are found to overdo dispositional attributions in a manner consistent with the â€œfundamental attribution errorâ€ first identified by Fritz Heider and extended by Thomas Pettigrew to inter-group prejudice as â€œthe ultimate attribution error.â€ A concluding discussion seeks to contextualize these partisan-based differences with reference to the divisive nature of President Trumpâ€™s leadership while identifying a way forward for further research.